Complementary and alternative medicine use: Results from a descriptive study of pregnant women in Udi local Government area of Enugu state, Nigeria - Jane-lovena Onyiapat; Chinyelu Okafor; Ijeoma Okoronkwo; Agnes Anarado; Ekene Chukwukelu; Ada Nwaneri; Pat Okpala (BMC, 2017)
Abstract Background The use of CAM by pregnant women is very popular in developed countries. The trend is increasing globally and lack of evidence of safety particularly when used during pregnancy may lead to complications. Pregnancy is a vulnerable period especially during the first trimester. There is scarcity of empirical evidence on CAM use particularly among women in Udi LGA of Enugu State and South East Nigeria. Moreover, studies carried out in Nigeria have been limited to herbal medicine use, which is one aspect of CAM. This study was designed to obtain information on the use of Complementary and Alternative Medicine among pregnant women. Methods The study was a cross sectional descriptive survey of 396 pregnant women systematically drawn from twenty political wards in Udi Local Government Area (LGA) of Enugu State. Interviewer administered questionnaire developed by the researchers was used for data collection. Data were analyzed using descriptive statistics. Results Majority (82.1%) of the pregnant women in Udi LGA used CAM during pregnancy out of which 53.8% had used CAM in previous pregnancies. CAM used ranges from one single type to sixteen different types with biological products eg, herbal tea, herbal mixture being the most commonly used CAM. Whereas most (89.5%) of the CAM used by pregnant women was consumed orally, approximately half of the pregnant women used CAM together with conventional medicine. Conclusion The use of CAM by women during pregnancy was high in Udi LGA. Therefore, maternity care providers especially midwives need to elicit CAM commonly used by women during pregnancy and counsel them appropriately for best care and safety. Researchers should focus on establishing the efficacy of CAM products.